Effect of Different Ratios of Yinchen and Gancao Decoction on ANIT-Treated Cholestatic Liver Injury in Mice and Its Potential Underlying Mechanism - Su, Huizong; Wang, Qian; Li, Yue; Jin, Jingyi; Tan, Bo; Yan, Dongming; Zou, Bin; Song, Guochao; Weng, Fengyi; Qiu, Furong (Frontiers in Pharmacology, 2021)
Cholestasis is a pathological state that leads to serious liver disease; however, therapeutic options remain limited. Yinchen and Gancao are often used in combination at different ratios in traditional Chinese formulae for the treatment of jaundice and cholestasis. In the present study, we investigated the effect of decoctions containing different ratios of Yinchen and Gancao (YGD) on alpha-naphthyl isothiocyanate (ANIT)-treated intrahepatic cholestasis (IC) in mice, and further explored the underlying mechanism. Treatment with 0:4 and 1:4 YGD significantly reduced plasma total bile acid (TBA), total bilirubin (TBIL), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) activities; decreased unconjugated and conjugated bile acid levels; and improved hepatocyte necrosis and inflammatory cells recruitment to hepatic sinusoids. Moreover, the expression levels of Toll-like receptor 4 (TLR4), interleukin-1β (IL-1β), IL-6, tumor necrosis factor alpha (TNF-α), C-C ligand 2 (CCL2), and C-X-C ligand 2 (CXCL2) in the liver were significantly reduced. However, treatment with 4:1 and 4:0 YGD increased plasma TBA, TBIL, AST, ALT, and ALP activities and aggravated liver cell injury and inflammation. Moreover, the mRNA expression of the bile salt export pump (BSEP) in the liver was significantly increased in mice treated with 4:0 YGD. The present study demonstrates that YGD containing a high proportion of Gancao, which inhibits the TLR4/NF-κB pathway and reduces the inflammatory response, had protective effects against ANIT-treated IC in mice. However, YGD containing a high proportion of Yinchen aggravated the ANIT-treated IC in mice, which may be related to upregulation of BSEP and boosting bile acid regurgitation from damage cholangiocytes to liver in ANIT-treated IC mice.